Novel drug discovery strategies for atherosclerosis that target necrosis and necroptosis. (3rd June 2018) - Coornaert, Isabelle; Hofmans, Sam; Devisscher, Lars; Augustyns, Koen; Van Der Veken, Pieter; De Meyer, Guido R.Y.; Martinet, Wim
ABSTRACT: Introduction : Formation and enlargement of a necrotic core play a pivotal role in atherogenesis. Since the discovery of necroptosis, which is a regulated form of necrosis, prevention of necrotic cell death has become an attractive therapeutic goal to reduce plaque formation. Areas covered : This review highlights the triggers and consequences of (unregulated) necrosis and necroptosis in atherosclerosis. The authors discuss different pharmacological strategies to inhibit necrotic cell death in advanced atherosclerotic plaques. Expert opinion : Addition of a necrosis or necroptosis inhibitor to standard statin therapy could be a promising strategy for primary prevention of cardiovascular disease. However, a necrosis inhibitor cannot block all necrosis stimuli in atherosclerotic plaques. A necroptosis inhibitor could be more effective, because necroptosis is mediated by specific proteins, termed receptor-interacting serine/threonine-protein kinases (RIPK) and mixed lineage kinase domain-like pseudokinase (MLKL). Currently, only RIPK1 inhibitors have been successfully used in atherosclerotic mouse models to inhibit necroptosis. However, because RIPK1 is involved in both necroptosis and apoptosis, and also RIPK1-independent necroptosis can occur, we feel that targeting RIPK3 and MLKL could be a more attractive therapeutic approach to inhibit necroptosis. Therefore, future challenges will consist of developing RIPK3 and MLKL inhibitors applicable in both preclinical and clinical settings.